Gluon scattering in AdS at finite string coupling from localization - Behan,C; Chester,SM; Ferrero,P (Journal of High Energy Physics, 2024)
A bstract We consider gluons scattering in Type IIB string theory on AdS 5 × S 5 / 2 in the presence of D7 branes, which is dual to the flavor multiplet correlator in a certain 4d $$ \mathcal{N} $$ N = 2 USp(2 N ) gauge theory with SO(8) flavor symmetry and complexified coupling τ . We compute this holographic correlator in the large N and finite τ expansion using constraints from derivatives of the mass deformed sphere free energy, which we compute to all orders in 1 /N and finite τ using supersymmetric localization. In particular, we fix the F 4 higher derivative correction to gluon scattering on AdS at finite string coupling τ s = τ in terms of Jacobi theta functions, which feature the expected relations between the SL(2 , ) duality and the SO(8) tria